Lead knee flexion angle is associated with both ball velocity and upper extremity joint moments in collegiate baseball pitchers - Solomito, M. J.; Garibay, E. J.; Cohen, A.; Nissen, C. W. (Sports Biomechanics, 2022)
An important aspect of the pitching motion is the lead leg knee angle, from initial lead foot contact to ball release, which can influence pitching performance and injury potential. Understanding the implication of this angle is essential to appropriately coach baseball pitchers. Therefore, the purpose of this study was to determine the lead leg knee flexion influence on both ball velocity and the elbow varus moment. Kinematic and kinetic data were collected using standard optoelectronic motion capture methods from 121 collegiate pitchers and analysed using a random intercept, mixed effects regression model to evaluate the association between the knee angle on peak ball velocity and peak elbow varus moment, independently. Statistically significant associations between the knee flexion angle and ball velocity as well as with the elbow varus moment were noted. The data indicated that a 10° increase in knee flexion at ball was associated with a 2.1 Nm reduction in the peak elbow varus moment (p = 0.021, r2 = 0.12) and a 0.2 m/s reduction in peak ball velocity (p = 0.010, r2 = 0.11). This study provides scientific evidence that the lead knee flexion angle influences both upper extremity stresses and ball velocity.